The effect of needle-punched nonwoven fabric thickness on electromagnetic shielding effectiveness - SANCAK, ERHAN; ÖZEN, MUSTAFA SABRİ (SAGE PUBLICATIONS LTD, 2015)
In this study, the effect of nonwoven fabric thickness on electromagnetic shielding effectiveness (EMSE) was investigated and there was found to be a correlation between the thickness of needle-punched nonwoven fabric and EMSE. The production of needle-punched nonwoven fabrics from stainless steel staple fiber in the experimental study was carried out. Stainless steel staple fibers provided by Bekaert were used as a raw material. The webs were formed using a wool-type carding machine. The webs were bonded using needling punching machines. The pre-needled, twice-needled and thrice-needled nonwoven fabrics at three different thicknesses were produced. The experimental studies were carried out using large-scale production machines instead of small-scale laboratory-type machines. EMSE measurements of produced needle-punched nonwoven fabrics, in addition to physical properties such as strength, elongation and thickness, were performed. The coaxial transmission line method specified in ASTM D4935-10 was utilized to test the nonwoven fabrics and the needle-punched nonwoven fabrics were tested in the frequency range from 15 to 3000 MHz. It was understood that needle-punched nonwoven fabric thickness was a very important parameter for EMSE. It was found that as the frequency increases, EMSE values of needle-punched nonwoven fabrics showed continuously increasing tendency by starting from a specific frequency in the frequency range of 15-3000MHz. There were no significant differences between absorption and reflection values of needle-punched nonwoven fabrics produced at different thicknesses. It was found that pre-needle-punched, twice-needled and thrice-needle-punched nonwoven fabrics produced from the conductive stainless steel staple fibers in our study have, respectively, highest EMSE values of 22, 25 and 27 dB between 2100 and 2400 high frequency ranges.
Keywords: needle punching; nonwoven fabric; electromagnetic shielding; stainless steel staple fiber; CARBON-FIBER